(untitled) (Journal of Atomic and Molecular Sciences, 2015)
The stereodynamics of the atom-molecule reaction N(^4S)+O_2(X^3Σ^-_g) → O(^3P) +NO(X^2Π) has been studied using quasi-classical trajectory method with the lowest ^2A' potential energy surfaces (PESs) given by Sayós et al. [R. Sayós, C. Oliva, M. González, J. Chem. Phys. 117 (2002) 670]. Four generalized polarization-dependent differential cross-sections [(2π/σ) (dσ_00/dω_t), (2π/σ)(dσ_20/dω_t), (2π/σ)(dσ_22+/dω_t), (2π/σ)(dσ_21-/dω_t)] and distributions P(θ_r), P(φ_r) were calculated. The effects of the different initial rotational and vibrational states were analyzed. It found that the degree of the forward scatting and the product polarizations show obviously change along with the initial vibration number, which leads to the increase of alignment and decrease orientation of product rotational angular momentum j'. Although the influence of the initial rotational excitation effect on the aligned and oriented distribution of product is not stronger than that of the initial vibration excitation effect, the initial rotational excitation makes the alignment of the product rotational angular momentum small change in a certain range. Moreover, the P(θ_r) distribution and P(φ_r) distribution change noticeably by varying the initial vibration number.